Proses Pengembangan Pariwisata Di Kota Surabaya Antara Pemerintah Dan Non Pemerintah Dalam Perspektif Tata Kelola Kolaboratif - Bayu Priambodo (Journal of Contemporary Public Administration, 2022)
The tourism industry has been most affected in the pandemic era. Until now, the development of the tourism industry, especially in big cities, has only focused on public and private sector actors. while in big cities there are two groups of people, namely local communities and urban communities. This community group has never participated in the tourism development process. The city of Surabaya is the second largest city in Indonesia, where the development of the tourism industry is quite massive. From these problems, the researcher wants to see how the process of developing Surabaya's tourism development process runs. Qualitative methods used in this research method, and data collection techniques with in-depth interviews. Ansell and Gash's collaborative governance theory was used in the data analysis of this study. The results showed that the cooperation of the city of Surabaya was not in sync with other players. This can be seen from the government itself which has two tourism promotion agencies, but these two institutions continue to operate independently. Even the people themselves are not involved in the tourism development process, this can be seen from the people who do not know when tourism development takes place in their place of residence. In turn, private individuals who act as developers in the development process do not use local communities as employees. It is clear that the management of cooperatives in Surabaya has not been effective.